DINA: Development Model Physical Activity of Dance Intensive Nimble Physical Activity for Children Aged 9-10 Years - Dina Firda Maula; Putra, Ranu Baskora Aji (Universitas Negeri Semarang (UNNES) in cooperation with ACPES (ASEAN Council of Physical Education and Sport), 2024)
Physical activity is vital for children to improve their motor skills and overall fitness. This study aimed to develop the Dance Intensive Nimble Activity (DINA), a physical activity model combining trending TikTok dances with short, high-intensity mini-games. The ADDIE model (Analyze, Design, Develop, Implement, Evaluate) guided the development. The study involved 68 children aged 9-10 years across Central Java and Yogyakarta schools, with data collected through observations, questionnaires, and documentation. Expert validation rated DINA as